The design of control strategies tolerant to unidentified failures in kinematically redundant manipulators - Balakrishnan, Venkataramanan, author; Maciejewski, Anthony A., author; Goel, M., author; IEEE, publisher (Colorado State University. Libraries, 1999)
The use of robots in hostile environments significantly increases the likelihood of failures in the robot's subsystems. Existing techniques for developing failure tolerant robots rely on effective failure detection and identification. Since failure identification is itself a difficult process that may not always be successful, it is important to consider the behavior of the robot prior to identification of a fault, or even the possibility of failures remaining unidentified. This work proposes control strategies that improve local measures of failure tolerance for kinematically redundant robots experiencing unidentified locked-joint failures. Measures to evaluate the fault tolerance capability of the various schemes are presented and the performance of the proposed schemes are demonstrated with an example.
Keywords: optimisation; redundant manipulators; control system synthesis; fault diagnosis; position control; fault tolerance; identification